2000
DOI: 10.1093/humrep/15.6.1250
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of tumour necrosis factor α in cultured granulosa cells from women with endometriosis

Abstract: Fertilization and oocyte cleavage rates have previously been demonstrated to be lower for women with endometriosis undergoing IVF compared with controls. This might be related to impaired oocyte function, possibly due to an inflammatory milieu in the pelvis of these women, where an elevated concentration of many cytokines is documented. The aim of this study was to examine whether granulosa cells from women with endometriosis deviated with respect to production of the inflammatory cytokines interleukin-1beta, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 32 publications
2
50
0
2
Order By: Relevance
“…Cell suspension consisted of GC colonies and singular cells, which may have included contaminating theca cells and fibroblasts. Therefore, according to Carlberg et al (2000), the cell suspension was passed through a cell strainer (size 40 μm; Becton Dickinson, Labora, Sweden). The retained cells obtained by back washing were counted in a Burker chamber using Trypan blue exclusion and plated in 24-well plates.…”
Section: Isolation Of Gcs From Follicular Aspirates and Cell Culturementioning
confidence: 99%
“…Cell suspension consisted of GC colonies and singular cells, which may have included contaminating theca cells and fibroblasts. Therefore, according to Carlberg et al (2000), the cell suspension was passed through a cell strainer (size 40 μm; Becton Dickinson, Labora, Sweden). The retained cells obtained by back washing were counted in a Burker chamber using Trypan blue exclusion and plated in 24-well plates.…”
Section: Isolation Of Gcs From Follicular Aspirates and Cell Culturementioning
confidence: 99%
“…The alteration of oocyte, granulosa, theca cells development and molecular follicular communication may impact on folliculogenesis. Carlberg (2000) found that granulosa cells of women with endometriosis have an upregulated production of IL-1 , IL-6, IL-8, TNF-which might be related to the reduced fertilization rate previously observed in endometriosis women (Carlberg et al, 2000). Beside that women with endometriosis were reported having higher granulosa cell apoptosis rate and a lower percentage of G2/M phase granulosa cells compared with other group of infertile women.…”
Section: Abnormal Folliculogenesis and Impaired Oocyte Functionmentioning
confidence: 79%
“…Cytokines, which are produced by many cell types in peritoneal fluid, play a diverse role as toxic effect in constructing the peritoneal environment that induces the development and progression of endometriosis and endometriosis-associated infertility (Harada et al, 2001). paracrine mechanisms (Carlberg et al, 2000) impair the granulosa cell function, oocyte maturation and folliculogenesis. Folliculogenesis is growth and development process of ovarian follicle consist of oocyte, granulosa and theca cells might result in mature and fertilizable oocyte (Rajkovic, 2006).…”
Section: Abnormal Folliculogenesis and Impaired Oocyte Functionmentioning
confidence: 99%
“…Macrophages secrete multiple cytokines that play an essential role in reproductive function. Dysregulation of macrophage number and function has been implicated in multiple ovarian and reproductive pathologies including polycystic ovarian syndrome [31], endometriosis [32], and premature ovarian insufficiency [29]. In a previous study of the effect of obesity on ovarian function, diet-induced obesity resulted in increased immune cell infiltration, and increased mRNA expression of inflammatory markers such TNFA, Rela, Il6 and the oxidative stress marker Nos2 in the ovaries and periovarian adipose tissue of obese mice, suggesting an important link between obesity and potentially HFD exposure and abnormal inflammatory responses in the ovary [33].…”
Section: Skaznik-wikiel Et Almentioning
confidence: 99%